PENGARUH SUHU TERHADAP STABILITAS SERTA PENETAPAN KADAR TABLET FUROSEMIDA MENGGUNAKAN SPEKTROFOTOMETER UV-VIS - Waney, Rekanita; citraningtyas, Gayatri; Abidjulu, Jemmy (PHARMACON, 2012)
Stability is the ability of product to maintain its nature and characteristics similar to itsorigin during storage and use period. Furosemide is one of drugs product that works as diuretic.The aim of this research was to study the effect of temperature on furosemide stability. Themethod using in this research is factorial Complete Random design. There are two factors in thisresearch,factor A is temperature (40oC, 50 oC, and 60 oC) and factor B are period (60, 120 and180 minutes). There are three samples in this research. Analysis of furosemide content usingSpectrophotometer UV-Vis at Î» = 271 nm. Obtained data were analyzed using spss ver. 20. Thedifferences between variable were statistical analyzed. The result shows that the decreasing offurosemide in tablet starts at temperature 50Â°Cafter60minutes heating for sample A and C.Sample B decrease at temperature 50Â°C after 120 minutes heating.Keywords: stability, furosemide, spectrophotometry UV-Vis